STRATEGI KOMUNIKASI PERLASI (PERSATUAN LAYANG LAYANG SELURUH INDONESIA) DALAM MENINGKATKAN KESADARAN PERMAINAN LAYANGAN - Ekasari, Ranti; Kusumawardhani, Leonita (Jurnal Ilmu Komunikasi PROGRESSIO, 2025)
This study aims to analyze PERLASI's marketing communication strategies to raise public awareness of the traditional kite game. The research adopts a descriptive qualitative method, with data collected through in-depth interviews with PERLASI's Chairman and members. The findings indicate that PERLASI effectively employs marketing strategies through social media, national-scale competitions, and collaborations with local communities. These strategies successfully engage younger generations while reinforcing cultural preservation. The application of the POAC management theory (Planning, Organizing, Actuating, Controlling) serves as a crucial foundation for aligning tradition preservation with the digital era. This study highlights how structured and innovative approaches can sustain traditional games as cultural identity symbols and cross-generational educational and recreational media.